An assessment of the quality of aerosol retrievals over the Red Sea and evaluation of the climatological cloud‐free dust direct radiative effect in the region. Issue 20 (20th October 2015) - Brindley, H.; Osipov, S.; Bantges, R.; Smirnov, A.; Banks, J.; Levy, R.; Jish Prakash, P.; Stenchikov, G.
Abstract: Ground‐based and satellite observations are used in conjunction with the Rapid Radiative Transfer Model (RRTM) to assess climatological aerosol loading and the associated cloud‐free aerosol direct radiative effect (DRE) over the Red Sea. Aerosol optical depth (AOD) retrievals from the Moderate Resolution Imaging Spectroradiometer and Spinning Enhanced Visible and InfraRed Imager (SEVIRI) instruments are first evaluated via comparison with ship‐based observations. Correlations are typically better than 0.9 with very small root‐mean‐square and bias differences. Calculations of the DRE along the ship cruises using RRTM also show good agreement with colocated estimates from the Geostationary Earth Radiation Budget instrument if the aerosol asymmetry parameter is adjusted to account for the presence of large particles. A monthly climatology of AOD over the Red Sea is then created from 5 years of SEVIRI retrievals. This shows enhanced aerosol loading and a distinct north to south gradient across the basin in the summer relative to the winter months. The climatology is used with RRTM to estimate the DRE at the top and bottom of the atmosphere and the atmospheric absorption due to dust aerosol. These climatological estimates indicate that although longwave effects can reach tens of W m −2, shortwave cooling typically dominates the net radiative effect over the Sea, being particularly pronounced in the summer, reaching 120 W m −2 at the surface. The spatial gradient in summertime AOD is reflected in the radiative effect at the surface and in associated differential heating by aerosol within the atmosphere above the Sea. This asymmetric effect is expected to exert a significant influence on the regional atmospheric and oceanic circulation. Key Points: Climatological aerosol optical depth (AOD) over the Red Sea is significant The climatological AOD shows a distinct seasonal and spatial pattern This manifests as asymmetric radiative surface cooling and atmospheric heating